POLA KOMUNIKASI ISLAM TERHADAP TRADISI HETERODOKS (Studi Kasus Tradisi Ruwatan) - Yanti, Fitri (Analisis: Jurnal Studi Keislaman, 2013)
Javanese  culture  are not  only provided  color in government  in Indonesia but also gives influence to religious practice. Java communities  who are predominantly  muslim can not leave their cultural traditions  until now day, even though sometimes it goes against  the Islamic worship (heterodox).  Ruwatan  is a worship that man saved from disruption  and disaster that threatens  their lives.  Through  ruwatan  people  feel  protected  by a large  force that  is believed  to be the power of the savior, this  phenomena continues until now. With add the Islamic shari’ah that does not prevent to implement ruwatan and morbidly eliminating the usual tradition  at the usual tradition  at the communicaties,  and do not deviate from the Islamic aqeedah and morals in the Al-qur’an and Hadits of prophet Muhammad. Shirk and bid’ah directed towards monotheism  and sunnah. The practice  include read surah Yasin by congregation, read tayyibah and prayers to our prophet. Say a prayer (pleading to Allah swt) in order to avoid our family from distress and given the salvation  of the world and the here after, held shadaqah/ charity   which was served to the participants  of the ceremony ruwatan